PELAKSANAAN PROGRAM KAMPUNG KELUARGA BERENCANA DI KELURAHAN NYAPAH KECAMATAN WALANTAKA KOTA SERANG - Siti Rohayati; Leo Agustino; Rina Yulianti (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2021)
The high birth rate has become a problem for Serang City from year to year, causing uncontrolled population growth. These factors are the background of the KB Village Program. The Office of Women's Empowerment, Child Protection, and Family Planning (DP3AKB) Serang City is the main organisation in charge of family planning issues in Serang City. Therefore, DP3AKB has sent a Family Planning Field Officer (PLKB) to implement the family planning program at the sub-district level. PLKB formed a KB Village Program Manager (PPK KB) so that villages could cooperate in finding and registering family planning acceptors by going directly to the field. The problems that occur in the implementation of the KB village program in Nyapah Village, Walantaka District are: lack of awareness of the people who are included in the fertile age couple (PUS) who have not become KB participants, lack of number and quantity of human resources in the KB village, Nyapah village, Walantaka district, lack of health facilities. in the Family Planning village, the lack of competence of the Pokja as implementers. The organization of the family planning village in Nyapah Village, Walantaka District, and community participation in the family planning village program in Nyapah Village has not been maximized. The purpose of this study was to describe the implementation of the Family Planning Village Program in Nyapah Village, Walantaka District, Serang City